2017
DOI: 10.1590/0037-8682-0454-2016
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus detection in pregnant women via culture and PCR methods

Abstract: Introduction: Group B Streptococcus (GBS), a source of neonatal infection, colonizes the gastrointestinal and genitourinary tracts of pregnant women. Routine screening for maternal GBS in late pregnancy and consequent intrapartum antibiotic prophylaxis have reduced the incidence of early-onset GBS neonatal infection. The aim of this study was to evaluate the performance of PCR, compared to culture (gold standard), in GBS colonization screening of pregnant women, and to establish the prevalence of GBS colonizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
2
20
0
4
Order By: Relevance
“…Although the revised CDC guidelines [1] recommend universal culture-based GBS screening between 35 and 37 weeks of pregnancy, the use of molecular methods as an additional rapid method of detection is encouraged. In concordance to our data, increased GBS detection rates by PCR assays compared to culture have been previously reported [15,23] with comparable results [5,6,8,24] or with lower colonization rates than the ones observed in this study [25]. However, previous data showed comparable performance of PCR method to culture [14].…”
Section: Discussionsupporting
confidence: 93%
“…Although the revised CDC guidelines [1] recommend universal culture-based GBS screening between 35 and 37 weeks of pregnancy, the use of molecular methods as an additional rapid method of detection is encouraged. In concordance to our data, increased GBS detection rates by PCR assays compared to culture have been previously reported [15,23] with comparable results [5,6,8,24] or with lower colonization rates than the ones observed in this study [25]. However, previous data showed comparable performance of PCR method to culture [14].…”
Section: Discussionsupporting
confidence: 93%
“…Culture-based methods remain the gold standard for GBS detection; however, numerous studies have suggested molecular methods, such as PCR, are more sensitive and specific compared to culture and represent a point-of-care detection option (El Helali et al 2009;de-Paris et al 2011;Khalil et al 2017;Wollheim et al 2017;Relich et al 2018). Cost-effectiveness is another consideration when evaluating screening methods, particularly in GBS where universal screening is implemented (Kaambwa et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The CDC guidelines also cite other laboratory tests for GBS detection, including PCR methods. PCR-based approaches are gaining a promising role in GBS detection, largely due to their higher sensitivity [6,13,18]. A European consensus statement noted that failure to treat GBS-positive mothers could lead to serious adverse neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%